2015
DOI: 10.1080/00015458.2015.11681099
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Enhanced Ultrasound (CEU) Using Microbubbles for Sentinel Lymph Node Biopsy in Breast Cancer: a Systematic Review

Abstract: CEU microbubble technique is an alternative technique of SLN detection in breast cancer patients. Further studies are necessary to standardize the method and clarify its specificity and sensitivity. Moreover, randomized control trials are suggested in order to compare this technique with the current techniques used for SLN detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…CEUS with microbubbles, based on the use of dispersion with sulphur hexafluoride gas injected intradermally around the areola, for sentinel node biopsy was first reported in 2013. In a subsequent meta‐analysis of five studies, this technique identified sentinel lymph nodes in 9·3–55·2 per cent of patients, with a sensitivity of 61–89 per cent and a false‐negative rate of 6·6–39 per cent. No comparative study of CEUS against the dual‐modality technique exists to validate this method.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS with microbubbles, based on the use of dispersion with sulphur hexafluoride gas injected intradermally around the areola, for sentinel node biopsy was first reported in 2013. In a subsequent meta‐analysis of five studies, this technique identified sentinel lymph nodes in 9·3–55·2 per cent of patients, with a sensitivity of 61–89 per cent and a false‐negative rate of 6·6–39 per cent. No comparative study of CEUS against the dual‐modality technique exists to validate this method.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we followed the rationale of guiding the CNB to the lymph node cortex, where early metastatic tumor deposits develop . However, the CEUS technique justifies and enables percutaneous CNB of small benign‐appearing lymph nodes with a very thin cortex . Limiting the 14‐gauge needle's trajectory to a thin cortex is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Such lymph nodes are more prone to substantial structural damage and disruption of the hilar blood flow after a 14‐gauge CNB, which may induce the development of perinodal fibrosis. On the other hand, it is unlikely that the contrast agent itself could cause perinodal fibrosis because microbubble destruction occurs within a short time frame . Moreover, there has been no report of clinical, sonographic, or pathologic evidence of fibrosis or scarring at the site of CEUS intradermal injection in previous CEUS + CNB studies …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations